Generation of Bioactive Hydrolysates and Peptides from Bovine Hemoglobin with In Vitro Renin, Angiotensin‐I‐Converting Enzyme and Dipeptidyl Peptidase‐IV Inhibitory Activities. Issue 5 (2nd March 2016) - Lafarga, Tomas; Rai, Dilip K.; O'connor, Paula; Hayes, Maria
Abstract: Bovine hemoglobin was selected for use in the generation of bioactive hydrolysates with potential for use as functional food ingredients for prevention of disorders such as hypertension, obesity and diabetes. Bovine hemoglobin was isolated and hydrolyzed with papain, which was selected using in silico analysis. The generated hydrolysate was enriched by ultrafiltration and further purified by high performance liquid chromatography. A number of peptides were identified using de novo peptide sequencing and these peptides were chemically synthesized to confirm their bioactivity in vitro . Three multifunctional peptides with both, ACE‐I and renin‐inhibitory properties and one peptide with ACE‐I‐inhibiting properties were identified. These included the di‐peptide HR with ACE‐I and renin IC50 values of 0.19 and 7.09 mM, respectively. The generated papain hydrolysate of bovine hemoglobin not only inhibited the enzymes ACE‐I and renin but also the enzyme DPP‐IV, which has been linked to type‐2 diabetes. Practical Applications: Slaughterhouse blood represents a problematic coproduct to meat processors due to the large volumes generated and its high pollutant load, and it is usually discarded as waste or used for low value purposes such as blood meal. However, bovine blood represents a valuable source of protein which is underused in the food industry. To find potential applications for this largely underutilized coproduct, the ACE‐I, renin and DPP‐IV inhibitory properties of a papain hydrolysate of bovine hemoglobin were studied and a number of novel multifunctional bioactive hydrolysates and peptides were identified. Results obtained herein may not only reduce blood disposal but also have a role in improving public health. In addition, this study demonstrates the potential of bovine hemoglobin as a resource for the generation of bioactive peptides and opens new commercial opportunities for its use beyond its current applications in the food industry.